Systematic Study of the Content of Phytochemicals in Fresh and Fresh-Cut Vegetables - María Isabel Alarcón-Flores; Roberto Romero-González; José Luis Martínez Vidal; Antonia Garrido Frenich (Antioxidants, 2015)
Vegetables and fruits have beneficial properties for human health, because of the presence of phytochemicals, but their concentration can fluctuate throughout the year. A systematic study of the phytochemical content in tomato, eggplant, carrot, broccoli and grape (fresh and fresh-cut) has been performed at different seasons, using liquid chromatography coupled to triple quadrupole mass spectrometry. It was observed that phenolic acids (the predominant group in carrot, eggplant and tomato) were found at higher concentrations in fresh carrot than in fresh-cut carrot. However, in the case of eggplant, they were detected at a higher content in fresh-cut than in fresh samples. Regarding tomato, the differences in the content of phenolic acids between fresh and fresh-cut were lower than in other matrices, except in winter sampling, where this family was detected at the highest concentration in fresh tomato. In grape, the flavonols content (predominant group) was higher in fresh grape than in fresh-cut during all samplings. The content of glucosinolates was lower in fresh-cut broccoli than in fresh samples in winter and spring sampling, although this trend changes in summer and autumn. In summary, phytochemical concentration did show significant differences during one-year monitoring, and the families of phytochemicals presented different behaviors depending on the matrix studied.